PENGARUH PENGGUNAAN MEDIA SCRAPBOOK DALAM BIMBINGAN KELOMPOK TERHADAP SELF-CONTROL PESERTA DIDIK KELAS VIII SMP NEGERI 1 JALANCAGAK - Ninda Nadia; Nandang Rukanda; Tuti Alawiyah (IKIP Siliwangi, 2023)
This study aims to determine the effect of using scrapbook media on self-control in class VIII SMP N 1 Jalancagak. The method used is descriptive method. The population in this study were 30 students. Data analysis using normality test and t test (paired sample test) using SPSS 26.0 program with a significance value (2-tailed) less than 0.005. The results of data analysis showed that the scrapbook media was in the very decent / good category with an average value of 86.86% of the questionnaire answers and the results of increasing self-control abilities obtained a percentage of 4.4%. While the results of the t-test analysis on the pre-test and post-test data obtained a significant value of 0.000. Thus, the results of this study indicate that: there is a positive influence between the use of scrapbook media on student self-control in class VIII SMP N 1 Jalancagak which can be categorized as quite high